Seeking the Historical Cook : Exploring Eighteenth-Century Southern Foodways - Moss, Kay (Book collections on Project MUSE., 2013)
"A guide to historical cooking techniques from eighteenth- and nineteenth-century receipt (recipe) books and an examination of how those methods can be used in kitches today"--Jacket.